Valuasi Kinerja Keuangan Dan Kinerja Saham (Studi Kasus PT Multistrada Arah Sarana Tbk). - Nikmah, Karimatun; Muktiadji, Nusa (LPPM Institut Bisnis dan Informatika Kesatuan, 2019)
This study aims to determine the effect of the company's financial performance on the company's stock performance. Based on the results of research, discussion and analysis conducted, it is known that overall company performance is affected by major problems namely due to slowing global economic conditions, oversupply of Chinese tires, weakening of the world currency against the USD and falling commodity prices of rubber being a factor decrease in sales volume and affect the amount of net profit generated by the company. Inefficiency in suppressing cost of goods sold and operating expenses also causes the erosion of operating profits generated by the company. So that it affects the financial performance and overall stock performance which also impacts the decline in the value of the company.